Removal of nitrates from wastewater using pond bottom soil - Erbanová, Evelína; Palarčík, Jiří; Slezák, Miloslav; Mikulášek, Petr (Politechnika Wrocławska, 2016)
The possibility of the final treatment of mine water from chemical leaching has been investigated. Despite water purification, high nitrate levels remain in these waters and must be removed. The main requirements are the lowest economic, operating and staffing levels. These requirements are best achieved by the removal of nitrates using biological methods, in our case using the pond bottom soil. Experiments were carried out in a batch mode. The effect of the environment on the denitrification process, the influence of the type and amount of the organic substrate and basic parameters of the denitrification such as redox potential, pH and dissolved oxygen were studied.
Odstranění dusičnanů z odpadních vod za použití půdy ze dna rybníka
Keywords: denitrification process; stabilization ponds; aquaculture ponds; nitrogen removal; nitrite; ratio; proces denitrifikace; odstranění dusičnanů; odpadní vody